Melon cultivation irrigated with saline waters promote chemical alterations in an acrisol (Bioscience Journal, 2020)
The objective of the present study was to evaluate the salinization process and the changes in the chemical properties of an Acrisol cultivated with melon irrigated with water of different saline concentrations. The experiment was carried out in the field conditions using the experimental design of randomized blocks, arranged in split-plot. The plots were composed of salinity levels of irrigation water, expressed in terms of water electrical conductivity (ECw): 0.54; 1.48; 2.02 dS m-1; and the sub-plots for melon cultivars: Sancho and Medellín (Toad Skin), Mandacaru (Yellow), Nectar (Galia) and Sedna (Cantaloupe). Soil samples were collected at the beginning and end of the crop cycle to evaluate the changes in the physical-chemical properties of the soil. The electrical conductivity of saturation extract in the soil profile varied for each cultivar, observing high salinity values in soils with cultivars with lower water demand (Sedna and Nectar). The salinity of the soil was lower than the electrical conductivity of the irrigation water in the treatments with high values of ECw. The soil pH values showed little reaction in relation to the initial values. The exchangeable sodium percentage values were approximate twice the sodium adsorption ratio of the saturation stratum.